Tanzawana flavomaculata (Hymenoptera, Ichneumonidae, Ctenopelmatinae), a new genus and species of parasitoid of Fagineura crenativora (Tenthredinidae, Nematinae), a serious pest of beech tree - Watanabe, Kyohei; Taniwaki, Tooru; Kasparyan, Dmitri (Zootaxa, 2015)
We describe a new genus, and a new species, of parasitoid—Tanzawana flavomaculata Watanabe & Kasparyan (Hymenoptera: Ichneumonidae: Ctenopelmatinae)—based on material collected in Honshu, Japan. As T. flavomaculata is found on Fagineura crenativora Vikberg & Zinovjev, 2000 (Hymenoptera: Tenthredinidae), a serious pest of beech tree, this parasitoid is an important natural enemy of F. crenativora that can be used for the biological control of this pest.